Decision Support System-like Task to Investigate Operators' Performance in Manufacturing Environments. Issue 5 (2020) - Mailliez, M.; Hosseini, S.; Battaïa, O.; Roy, R.N.
Abstract: Modern manufacturing environment is very stressful for operators in charge of the production process. Unexpected events may deteriorate their performance by increasing their stress and workload. To help them, several tools have been developed. Nowadays, these decision support systems (DSS) are assumed to reduce operators' workload and stress because they automatically reschedule the production by applying algorithms. However, from a neuroergonomic perspective, findings remain equivocal. The effect of DSS has only been reported at a subjective level. As modern manufacturing environment is increasingly using intelligent systems like DSS to help operators in their decisions, it is important to understand how they can contribute to improve operators' performance. We aim to present a graphic interface and its associated experimental protocol investigating the operators' mental state using DSS and facing disruptions within a neuroergonomic perspective